Answer:
1. 2/3
2. (y-3)/x
3. y=(2/3)x+3
Step-by-step explanation:
I just did this assignment, and these are the correct answers!
Answer:
The two solutions of the equation is (0,-4)(6,0).
Answer:
f(x) = 3(x + 8)(x - 2)
Step-by-step explanation:
The intercept form of a quadratic function is y = a(x - r)(x - s), where r and s are the x-intercepts and a is the vertical stretch/compression factor.
If the intercepts are at (-8, 0) and (2, 0), and the vertical stretch is 3, just substitute these values into the intercept form formula, and you're done!
Please mark as Brainliest! :)
Answer:
y = 2
Step-by-step explanation:
Given
+ 4 = 6 ( subtract 4 from both sides )
= 2 ( cube both sides )
3y + 2 = 2³ = 8 ( subtract 2 from both sides )
3y = 6 ( divide both sides by 3 )
y = 2
That would be 3AB because of the expression you have